2014
DOI: 10.1155/2014/298767
|View full text |Cite
|
Sign up to set email alerts
|

Desmopressin Acetate in Intracranial Haemorrhage

Abstract: Introduction. The secondary increase in the size of intracranial haematomas as a result of spontaneous haemorrhage or trauma is of particular relevance in the event of prior intake of platelet aggregation inhibitors. We describe the effect of desmopressin acetate as a means of temporarily stabilising the platelet function. Patients and Methods. The platelet function was analysed in 10 patients who had received single (N = 4) or multiple (N = 6) doses of acetylsalicylic acid and 3 patients (control group) who h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…The standard dose is 0.3 μg/kg diluted in 50 ml saline and infused over 30 min [ 564 ]. Recently, two small prospective studies have shown that desmopressin can improve platelet function in patients with ICH who have received aspirin [ 567 ] or not [ 568 ] prior to the event. Identification of impaired platelet function with a platelet function analyser PFA-100 [ 559 ] or whole blood MEA [ 560 ] might be helpful in the identification of patients who could benefit from desmopressin therapy.…”
Section: Resultsmentioning
confidence: 99%
“…The standard dose is 0.3 μg/kg diluted in 50 ml saline and infused over 30 min [ 564 ]. Recently, two small prospective studies have shown that desmopressin can improve platelet function in patients with ICH who have received aspirin [ 567 ] or not [ 568 ] prior to the event. Identification of impaired platelet function with a platelet function analyser PFA-100 [ 559 ] or whole blood MEA [ 560 ] might be helpful in the identification of patients who could benefit from desmopressin therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Desmopressin (0.4 μg/kg IV given over 30 minutes) increased platelet activity, as measured by von Willebrand factor antigen and closure times (PFA-100 with epinephrine), 1 hour after DDAVP administration. The DDAVP effect may be short lived, however, and platelet function abnormalities may return within 3 hours [ 110 ]. Based on these limited data, a single dose of DDAVP (0.4 μg/kg IV given over 30 minutes) may be considered for patients with aspirin-associated, COX-1 inhibitor-associated, or ADP receptor inhibitor-associated ICH.…”
Section: Medical Management Of Ichmentioning
confidence: 99%
“…Platelet transfusion and coadministration of DDAVP has not been associated with a decreased risk of hemorrhage progression or mortality. In a prospective study, 14 DDAVP was administered to 10 patients with ICH who had been receiving ASA, and platelet function was improved; this effect was short-lived and not statistically significant. Naidech et al 15 reported a study in patients with spontaneous intracerebral hematoma and reduced platelet activity.…”
Section: Treatmentmentioning
confidence: 99%